Sakralitas Pawiwahan Hindu: Analisis Teologi Seksual - Suda, Gede (PANGKAJA: JURNAL AGAMA HINDU, 2020)
God is the creator of this world and its contents, he also regulates the system of life and death, he is the almighty, with the power of all living things can develop and have instincts to have offspring, as well as humans as one of His creatures, then, sexual relations are as a form of human activity that is natural has been embedded since birth. Naturally everything is created mutually in pairs, Rwa Bhineda, complementary, bivalence is God's will and sex constitutes the relationship between women and men, is the implementation of His will. Sex is the most foundational foundation of the continuity of human existence. With human sex it will continue to exist. Therefore sex is a sacred dimension of human life. Apart from being sacred, sex is also a sacred act of mankind to give birth to offspring, a process of creation, which combines masculine and feminine cosmic principles. Sex that is said to be sacred and sacred must go through several stages, such as marriage, and practice the teachings of the holy vedas, so that later from the results of a sacred marriage and sacred sex rituals, undoubtedly can give birth to children who are supernatural, besides, sex is also a means ritual for as self-union with God.Â